A Switching Signal Remote Detection Method Based on A/D Transformation - Jianpo LONG; Shuqing WANG; Changzhi LYU (机车电传动)
In order to solve the problem of the fluctuation of voltage signal and abnormal recognition in switch signal transmission of the railway monitoring equipment remote monitoring system, the main concepts of remote detection of switching volume were analyzed, a new design idea, which used analog signal detection and A/D conversion, was proposed, and the circuit design was completed. The field test showd that the designed circuit could realize remote accurate detection and communication of switching quantity in low voltage monitoring system, and the system run stably and reliably.